Control point locating scheme of street light network in urban environment - Yue-Shan Chang; Ruey-Kai Sheu; Guang-Ting Wu (International Journal of Distributed Sensor Networks)
Energy conservation is the top-priority policy for public street light infrastructure construction in recent years. Traditional periodically always-on policy guarantees the brightness for dark nights, but it consumes most energy and wastes a lot of money. Hence, there are strong demands to intelligently manage the construction and control over street light infrastructures. In this article, a scheme for locating the control point of street light network in urban district is proposed to replace the conventional always-on policy based on the geographic information of an urban environment. We first exploit the geographic map of an urban district to estimate the total number of street lights, and then partition the district into several adaptive blocks. Finally, the control point of each partitioned block is found and the connection of all street lights is established. Some experiments have been conducted to evaluate the performance and the feasibility of the proposed scheme. And the experimental results demonstrate that the proposed scheme is very reliable and efficient to construct the street light network of urban district.